Social contextual risk factors for stimulant use among adolescent American Indians. (1st October 2017) - Spillane, Nichea S.; Weyandt, Lisa; Oster, Danielle; Treloar, Hayley
Highlights: We know very little about stimulant misuse among American Indian (AI) adolescents. Being prescribed stimulants increases the likelihood of using misusing stimulants. Being prescribed stimulants increase the frequency of past month stimulant use. Other important factors included social, contextual factors, peers and family. Professionals who prescribe stimulants should be aware of the abuse potential. Abstract: Objective: Stimulants are the most common and efficacious treatment for Attention-Deficit Hyperactivity Disorder (ADHD). We examined the relationship between stimulant misuse and social factors that could be malleable to prevention among American Indian (AI) adolescents. Method: Participants were AI students (N = 3498) sampled from 33 schools in 11 states. Participants completed the American Drug and Alcohol Survey. A multilevel analytic approach was used to evaluate the effects of participant-level (level 1) variables (i.e., gender, grade, peer, school, family, stimulant prescribed by doctor) on lifetime and current simulant use to 'get high.' Results: Nearly 7% of our sample had been prescribed stimulants and nearly 6% of the sample reported using stimulants to get high. Age [OR = 1.22; 95% CI = 1.09, 1.36, p < 0.001 ], perception of peer substance use [OR = 1.19; 95% CI = 1.14, 1.23, p < 0.001], parental monitoring [OR = 0.96; 95% CI = 0.92, 1.99, p = 0.04], and stimulants prescribed by a doctor [OR = 8.79, 95% CI = 5.86, 13.18, p < 0.001] were associated with ever using stimulants to get high. Perception of peer substance use, [ b = 0.09, SE = 0.02, p < 0.001, 95%CI [0.05, 0.13], and having stimulants prescribed by a doctor, [ b = 0.58, SE = 0.21, p = 0.006, 95%CI [0.17, 0.99], were associated with frequency of past month use to get high. There was also a significant quadratic effect for parental monitoring, suggesting that low and high levels were associated with increased stimulant use. Conclusions: Our results suggest a need for prevention efforts to be directed to AI youth who are prescribed stimulants.